2011
DOI: 10.1016/j.palaeo.2010.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemical processes controlling oxygen and carbon isotopes of diatom silica in Late Glacial to Holocene lacustrine rhythmites

Abstract: Biogeochemical cycles and sedimentary records in lakes are related to climate controls on hydrology and catchment processes. Changes in the isotopic composition of the diatom frustules (δ 18 O diatom and δ 13 C diatom ) in lacustrine sediments can be used to reconstruct palaeoclimatic and palaeoenvironmental changes. The Lago Chungará (Andean Altiplano, 18°15′S, 69°10′W, 4520 masl) diatomaceous laminated sediments are made up of white and green multiannual rhythmites. White laminae were formed during short-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…C. andinus was first described from Lake Titicaca and was originally thought to be endemic to the basin. Subsequently, it has been reported from other Andean fossil locations and in one contemporary site Ekdahl et al, 2008;Hernandez et al, 2011). These data suggest that the taxon occurs outside the Lake Titicaca basin, although its distribution appears to be restricted to the tropical Andes.…”
Section: Diatom Evolution and Extinctionmentioning
confidence: 71%
“…C. andinus was first described from Lake Titicaca and was originally thought to be endemic to the basin. Subsequently, it has been reported from other Andean fossil locations and in one contemporary site Ekdahl et al, 2008;Hernandez et al, 2011). These data suggest that the taxon occurs outside the Lake Titicaca basin, although its distribution appears to be restricted to the tropical Andes.…”
Section: Diatom Evolution and Extinctionmentioning
confidence: 71%
“…There is a former appreciable knowledge of the main changes that occurred in the lake since the Late Glacial based on multiproxy evidence. These included sedimentary facies characterization (Sáez et al, 2007), isotopic composition of bulk organic matter (δ 13 C org , δ 15 N org ; Pueyo et al, 2011), carbonates (δ 18 O carbonate , δ 13 C carbonate ; Pueyo et al, 2011), and diatom frustules (δ 18 O diat , δ 13 C diat ; Hernández et al, 2008Hernández et al, , 2010Hernández et al, , 2011Hernández et al, , 2013, as well as a moisture balance reconstruction based on magnetic susceptibility, X-ray Fluorescence (XRF), X-ray Diffraction (XRD), Total Carbon and Total Organic Carbon (TC and TOC),…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade researchers have paid special attention to investigating past climate changes and factors leading to switches between glacial and interglacial conditions. Numerous studies have shown the transition from cold and dry glacial to warm and wet interglacial climate led to major environmental alterations in the terrestrial part of lake catchments and in aquatic ecosystems (Morley et al, 2005;Stebich et al, 2009;Müller et al, 2010;Hernandez et al, 2011;Cook et al, 2012;Zhao et al, 2013).…”
Section: Introductionmentioning
confidence: 99%